2013
DOI: 10.1371/journal.pone.0070117
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin and Doxorubicin Induce Distinct Mechanisms of Ovarian Follicle Loss; Imatinib Provides Selective Protection Only against Cisplatin

Abstract: PurposeChemotherapy treatment in premenopausal women has been linked to ovarian follicle loss and premature ovarian failure; the exact mechanism by which this occurs is uncertain. Here, two commonly used chemotherapeutic agents (cisplatin and doxorubicin) were added to a mouse ovary culture system, to compare the sequence of events that leads to germ cell loss. The ability of imatinib mesylate to protect the ovary against cisplatin or doxorubicin-induced ovarian damage was also examined.Experimental designNewb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
126
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(132 citation statements)
references
References 52 publications
4
126
0
2
Order By: Relevance
“…To test these hypotheses, we used gene therapy with MIS, or rhMIS parenteral protein administration, to create a complete arrest in primordial follicle activation concurrently with chemotherapy cycles. As a proof of concept we chose three commonly used chemotherapeutic classes with well-described gonadotoxicities: platinums (54), anthracyclins (55), and alkylating agents (56). Both platinums (such as CBP) and anthracyclins (DOX) interfere with DNA replication and as such are particularly toxic to dividing granulosa cells of secondary and antral follicles, albeit with distinct toxicity profiles (55), and thus represent ideal targets for an MIS oncofertility intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To test these hypotheses, we used gene therapy with MIS, or rhMIS parenteral protein administration, to create a complete arrest in primordial follicle activation concurrently with chemotherapy cycles. As a proof of concept we chose three commonly used chemotherapeutic classes with well-described gonadotoxicities: platinums (54), anthracyclins (55), and alkylating agents (56). Both platinums (such as CBP) and anthracyclins (DOX) interfere with DNA replication and as such are particularly toxic to dividing granulosa cells of secondary and antral follicles, albeit with distinct toxicity profiles (55), and thus represent ideal targets for an MIS oncofertility intervention.…”
Section: Discussionmentioning
confidence: 99%
“…As a proof of concept we chose three commonly used chemotherapeutic classes with well-described gonadotoxicities: platinums (54), anthracyclins (55), and alkylating agents (56). Both platinums (such as CBP) and anthracyclins (DOX) interfere with DNA replication and as such are particularly toxic to dividing granulosa cells of secondary and antral follicles, albeit with distinct toxicity profiles (55), and thus represent ideal targets for an MIS oncofertility intervention. CPA is an alkylating agent, a class that is particularly damaging to germ cells, and is the most problematic gonadotoxic chemotherapeutic in the clinic, particularly because it is often used in young girls with hematological cancers (57).…”
Section: Discussionmentioning
confidence: 99%
“…Cancer treatment with DNA alkylating agents, such as cyclophosphamide (CP) and Ifosfamide (IFO) and Cisplatin can lead to gonadotoxicity, impaired fertility, ovarian failure, resulting in premature menopause (1)(2)(3).…”
Section: Issn 2330-4456mentioning
confidence: 99%
“…Mitochondria which function to generate energy by oxidative phosphorylation, are known as one of the main endogenous sources of ROS. Studies reported that exposure to cisplatin leads to a significant increase in intracellular ROS (3). A few others reported that treatment with antioxidants attenuates the cytotoxic effects of cisplatin on different organs, suggesting an involvement of oxidative stress in the pathogenesis of cisplatin-induced cytotoxicity which also seen in reproductive system (7).…”
Section: Issn 2330-4456mentioning
confidence: 99%
“…Chemotherapeutic agents can also lead to POF in women during their reproductive years, and can therefore affect their future fertility. The risk for developing POF appears to be dependent upon the exact nature of the chemotherapeutic regimen, and includes factors such as drug dosage and patient age (Morgan et al, 2013). Recent studies have documented the induction of ovarian dysfunction as a result of cisplatin, including menstrual disorders, premature menopause, and infertility (Chen et al, 2015;Li et al, 2013.…”
Section: Introductionmentioning
confidence: 99%